A Comparative Photophysical and Photochemical Study of Nitropyrene Isomers Occurring in the Environment - Pino-Lopez, E (2011)
Ground state absorption, first excited-singlet state, and properties of reactive intermediates of mononitropyrene isomers encountered in the atmospheric aerosol have been studied under different conditions that could mimic the environment. The nitro group can present different orientations relative to the pyrene ring depending on its geometric location and could induce differences in the photochemistry of the isomers. The 2-NO2Py isomer has the largest red shift and lowest oscillator strength in the UV-visible band associated with the nitro group. The isomers show very low fluorescence yields (10 -3-10-4). Only 1-NO2Py and 4-NO2Py have phosphorescence emission (?p ? 10-4), indicating that the lowest triplet state decays mainly through effective radiationless channels. Laser photolysis produces a low-lying triplet state (?T = 10-5-10-6s), a long-lived pyrenoxy radical, and a PyNO2H radical in solvents in which the triplet can abstract a hydrogen atom. Similar triplet yields were calculated (0.1-0.6) for the isomers, while significant differences in the relative yield of the long-lived species were determined. Differences in the quenching rate constants of the triplet by water and phenols suggest a strong hydrogen-bond interaction with the nitro group in the C-2 position, which provides for radiationless deactivation routes. © 2010 American Chemical Society.